Kustaanheimo-Stiefel استخدام الحل التحليلي لمعادلات الحركة للقمر الاصطناعي في إيجاد العناصر البعدية للمدار بواسطة نظرية - علي عبد الزيدي, مهند (University of Thi-Qar Journal of Science, 2010)
In this paper the analytic solution for equation of the satellite motion is used to find the Dimension elements for the orbit represented by Semi-major axis and eccentricity, this is done by the effect of the second harmonic J ب 2 of short term orbit for three initial conditions it is seen from it that the increasing in the eccentricity associated with increasing of semi major axis, which proved that the linear relationship between them. These factors have been calculated using K-S theory which summarized in calculating the coefficients resulted from analytical integral for differential equationusing coefficients called K-S. Kustaanheimo-Stiefel theorem is summarized inestimation the coefficients resulted from the solution of the ordinary differential equation. The procedure is shown in two steps: firstly, the calculation of the initial conditions according to their relation with the distances and velocity of the satellite. Secondly, the analytical solution is achieved to finding these coefficients (α,β,λ,λ*).